Performance analysis of substation automation systems architecture based on IEC 61850 - Kumar, S.; Das, Narottam; Islam, Syed (Institute of Electrical and Electronics Engineers Inc., 2014)
© 2014 ACPE. Digital Communications amongst multi-vendor intelligent electronic devices (IED's) is an important feature of a substation automation system (SAS). Measuring the propagation delays and assessing the interoperability performance of IED's in an Ethernet architecture play a critical role in the protection of important substation assets. Early detection of the loss of data packets in a star connected Ethernet architecture is an important step towards identification of delay in message transfer issue. This identification of the problem could lead to reliable operation of protection system and better understanding of the issues of interoperability which may improve the protection system from safety and availability point of view. This paper focuses on a star connected architecture using Optimized Network Engineering Tool (OPNET) software for a 132/22kV zone substation. It shares a practical case for measuring delay time in exchanging Generic Object Oriented Substation Event (GOOSE) messages amongst the IED's.